Utilización de reconocimiento facial para optimizar la gestión de control de asistencia en los laboratorios de la Facultad de Administración, Finanzas e Informática. - Arias Moran, José Manuel (2023)
Technological advances have been remarkable in recent years, this progress has not been limited to electronic devices but has also affected the way in which human beings carry out their daily lives. At present, people are surrounded by technology, either to carry out their work activities or for leisure and security, both personal and of their belongings. With the arrival of new technologies, surveillance cameras have experienced significant advances, since now they are not limited only to video capture but also have the ability to detect patterns and physiological parameters. Biometric-based pattern detection provides a novel tool for users, which will be able to identify people passing through a given area; In this way, access control could be carried out to particular areas of an establishment in which the passage is restricted or limited to certain users in particular and in case of an accident or unforeseen event, have a list of people who were present at the time of the incident. event. This research project was born from the need to use facial identification and authentication technology to optimize the control and management of assistance in the laboratories of the Facultad de Administración, Finanzas e Informática (F.A.F.I).